1973
DOI: 10.1007/bf01249360
|View full text |Cite
|
Sign up to set email alerts
|

The growth of Semliki Forest virus in cultured mosquito cells: Ultrastructural observations

Abstract: Togaviruses (8) replicate in both their vertebrate and invertebrate hosts. Recent studies in these two systems show that the initial growth kinetics of two representative Mphaviruses (8), Semliki Forest virus (1, 2) and Ross River virus (5) are similar in cultured vertebrate and invertebrate (Aedes albopictus) cells. However in the vertebrate cell infection results in cell death whereas in the mosquito cell the rate of cell division is unaltered and a persistent infection results (2, 4, 5).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

1974
1974
2015
2015

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 5 publications
1
12
0
Order By: Relevance
“…It is well known that the outcome of infection is fundamentally different between the two hosts, as mammalian infection is acute whereas arthropod infection creates a persistent infection (5,6,(8)(9)(10)(40)(41)(42). Perhaps these differences between the host species, for instance, the shutoff of host macromolecular synthesis, are a determinant of noncapped viral RNA production.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that the outcome of infection is fundamentally different between the two hosts, as mammalian infection is acute whereas arthropod infection creates a persistent infection (5,6,(8)(9)(10)(40)(41)(42). Perhaps these differences between the host species, for instance, the shutoff of host macromolecular synthesis, are a determinant of noncapped viral RNA production.…”
Section: Discussionmentioning
confidence: 99%
“…Togaviruses are maintained in nature as a result of transmission between vertebrate hosts by haemophagous arthropods; they multiply in both their vertebrate and invertebrate hosts (Dalgarno & Davey, 1973). Infection of cultured vertebrate cells by alphaviruses is generally cytopathic, whereas infection of cultured mosquito cells generally results in a persistent infection with little evidence of c.p.e.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, Enzmann (I973) concluded that the maintenance of the cell-virus equilibrium in Sindbis-infected Aedes albopictus cells was related to the presence of interferon-like substances. Ultrastructural studies show that during SFV and Ross River virus (RRV) infection of cultured A. albopictus cells, virus maturation may occur both at the cell membrane and within dense, membrane-bound, cytoplasmic inclusions (Raghow, Davey & Dalgarno, 1973 a;Raghow et al ~ 973 b). This is noteworthy since a characteristic feature of the mumps virus carrier state in mammalian cells is the localization of virus-specific antigens in a small number of discrete, cytoplasmic masses (Walker & Hinze,I962).…”
Section: Introductionmentioning
confidence: 99%
“…The outcome of alphaviral infection is dependent on the host system (6)(7)(8)(9)(10)(11)(12). Infection of mosquito cells does not result in the shutoff of host macromolecular synthesis and often culminates in persistent infection for the majority of mosquito cell lines (12)(13)(14)(15). Nevertheless, cell death as a result of infection has been reported for several members of the genus in whole mosquitoes (16)(17)(18)(19)(20)(21).…”
mentioning
confidence: 99%